Identitas Visual Padang Photo Sports - Ahmad Triyanda; San Ahdi (Lembaga Pengembangan Kinerja Dosen, 2023)
Padang Photo Sports is a photography service business in the field of sports. All types of sports can be documented by Padang Photo Sports such as basketball, volleyball, badminton, table tennis, futsal, and soccer. The purpose of designing Padang Photo Sports Visual Identity is to inform the public, especially those who like to play sports, that in Padang there are the latest photography services in the field of sports. The method applied to the design of Padang Photo Sports Visual Identity uses the 4D design method which stands for Define, Design, Develop, Disseminate to develop the design and uses the SWOT Analysis method which stands for Strengths, Weaknesses, Opportunities, and Threats to make it easier to find the value of a business and service. The orientation of the development of this Visual Identity design idea includes supporting media Stationery, Social media and Gift/merchandise. It is hoped that the design of this Visual Identity can help create opportunities and public awareness of photography services in the field of sports so that the design results can be right on target, effective, and communicative.